Comparison of the Efficacy and Safety of Extracorporeal Shock Wave Lithotripsy and Flexible Ureteroscopy for Treatment of Urolithiasis in Horseshoe Kidney Patients: A Systematic Review and Meta-Analysis - Yi, Xianyanling; Cao, Dehong; You, Pinghong; Xiong, Xingyu; Zheng, Xiaonan; Jin, Tao; Peng, Ge; Xu, Hang; Liao, Dazhou; Wei, Qiang; Li, Hong; Yang, Lu; et al. (Frontiers in Surgery, 2021)
BACKGROUND: Urolithiasis is the most common complications of Horseshoe kidney (HK), which can be treated by extracorporeal shock wave lithotripsy (ESWL), flexible ureteroscopy (FURS) and percutaneous nephrolithotomy (PCNL). When comparing treatments of ESWL and FURS, it is unclear which is more efficient and safety. The objective of this study was to compare the efficacy and safety of FURS and SWL for treatment of urolithiasis in horseshoe kidney patients. METHODS: A systematic search of the Web of Science, PubMed, EMBASE was performed in Feb.2021. Newcastle-Ottawa Scale (NOS) was used to assessed the risk of bias in each study. RESULTS: 5 studies published between 2008 and 2018 were synthesized in the present meta-analysis. The study revealed that FURS compared with SWL had greater initial and overall stone free rates (SFRs). Risk ratios (RRs) were 2.46 (P < .00001) in initial SFRs, 1.36 (P = 0.02) in overall SFRs. No differences were found in the retreatment ratio, RRs were 0.49 (P = 0.43). In addition, no major complications were encountered, and all the complications were mild to moderate. CONCLUSION: The study demonstrated that FURS and SWL are effective and safe treatment for HK patients with stone (<20mm). Moreover, FURS has greater clearance rates and lower complication rates than SWL.